The Dark Side of Solidarity: Ambivalences and Double Standards in the Ukrainian Refugee Crisis in Italy - Bolzoni, Magda; Donatiello, Davide; Giannetto, Leila (PARTECIPAZIONE E CONFLITTO, 2023)
The Russian invasion of Ukraine in 2022 and the subsequent arrival of people fleeing the war prompted remarkable mobilizations and responses throughout the EU. By focusing on the Italian context and, more specifically, on the case of the Piedmont Region, this paper conducts critical reflection on the different forms and expressions of solidarity that emerged at both the institutional and civic society levels. The paper builds on qualitative interviews carried out between February 2022 and March 2023 with representatives of public institutions, third-sector organisations, and associations, and it intends to: I) frame the different expressions of solidarity in light of recent changes in the regulatory arrangements of the institutional asylum system; II) explore the relationship between formal and informal reception with respect to equity in terms of conditions, opportunities, and quality of the services provided; III) discuss the implications of the double standards and the ambivalent role of solidarity towards a specific category of refugees, especially as regards its sustainability over time and the growing fragmentation of the refugee reception systems.